An Investigation of the Short-Term Effects of Intensive Management of Inpatients Aged 65 Years and Over with Severe Dysphagia: A Comparison of Inpatients 74 or Under with Those 75 and Over - UYAMA, Risa; YAMASHITA, Yukari; YOKOYAMA, Kaoru; TAKEI, Yoshiko; TAKAHASHI, Koji; AYANO, Rika (The Japanese Journal of Dysphagia Rehabilitation, 2011)
The management of dysphagia for both outpatients and inpatients has been carried out since the Department of Oral Rehabilitation, School of Dentistry, Showa University was established on June 1, 2004. This paper reports the effectiveness of intensive management of severe dysphagic inpatients aged 65 years or over.A comparison of inpatients aged 74 years or under with those 75 years or over hospitalized at some time from June 2004 to March 2009 was performed. The subjects were 14 patients, including 7 inpatients aged 74 years or under (average 69.4 y) and 7 inpatients 75 years or over (average 81.3 y). Age, gender, cause of dysphagia, period of hospitalization, time from dysphagia onset to hospitalization in our hospital, number of videofluoroscopic examination of swallowing (VF), method of dysphagia rehabilitation, feeding method, diet modification, daily kilocalories consumed and feeding level were investigated.Causes of dysphagia were cerebrovascular accidents (CVA) in three patients and post-surgical head and neck cancer (HNC) in four patients in those aged 74 years or under. CVA in two patients, HNC in one patient, dementia in two patients, progressive supranuclear palsy (PSP) in one patient and another disease in one patient were causes of dysphagia in the 75-years-and-over group.The average period of hospitalization for inpatients aged 74 years or under was 14.0 days and that for inpatients aged 75 years or over was 13.4 days. The shortest period from dysphagia onset to hospitalization in our hospital was 62 days and the longest period was 1,329 days (3 years and 8 months). The average number of attempts at VF examination during hospitalization was 2.4 times. Diet level was improved in 10 subjects (six 74 years or under patients and four 75 years or over patients). The amount of kilocalories consumed in one day increased in nine subjects (three 74 years or under patients and six 75 years or over patients). These results verify the effectiveness of our dysphagia program for intensive management of inpatients with severe dysphagia.